2017
DOI: 10.5194/bg-2017-16
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional-scale lateral carbon transport and CO<sub>2</sub> evasion in temperate stream catchments

Abstract: <p><strong>Abstract.</strong> Inland waters play an important role in regional to global scale carbon cycling by transporting, processing and emitting substantial amounts of carbon, which originate mainly from their catchments. In this study, we analyzed the relationship between terrestrial net primary production (NPP) and the rate at which carbon is exported from the catchments in a temperate stream network. The analysis included more than 200 catchment areas in south… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…These findings suggest that soil organic C content and NPP act as integrators of broad climate, hydrologic, and biogeochemical regional features, all of which relate one way or another to carbon available for export to the fluvial network, and which could be useful predictors of export in remote areas and with climate change scenarios. DIC did not show any geographical pattern related to NPP or climate, but there a nevertheless clear cross-regional differences in average riverine DIC, which are driven by large-scale patterns in underlying geology, as has been shown before (Giesler et al, 2014;Jantze et al, 2015;Magin et al, 2017;Wallin et al, 2014).…”
Section: Regional Structure Of Fluvial Dissolved Carbonmentioning
confidence: 50%
See 3 more Smart Citations
“…These findings suggest that soil organic C content and NPP act as integrators of broad climate, hydrologic, and biogeochemical regional features, all of which relate one way or another to carbon available for export to the fluvial network, and which could be useful predictors of export in remote areas and with climate change scenarios. DIC did not show any geographical pattern related to NPP or climate, but there a nevertheless clear cross-regional differences in average riverine DIC, which are driven by large-scale patterns in underlying geology, as has been shown before (Giesler et al, 2014;Jantze et al, 2015;Magin et al, 2017;Wallin et al, 2014).…”
Section: Regional Structure Of Fluvial Dissolved Carbonmentioning
confidence: 50%
“…The consistency between the modeled and measured values with NPP and lack of consistency with soil carbon content ( Figures S3-S5) suggest that NPP is a more effective integrator of climate and environmental factors, and may provide a better index of the active carbon pools that is mobilized into the fluvial network than soil C content. A recent study by Magin et al (2017) found a narrow range of C-export per terrestrial NPP in temperate watersheds and a meta-analysis suggesting that terrestrial-aquatic coupling may be predictive at large scales. Further development of such relationships in the future could be useful for improving global estimates of C-export and emissions which are highly uncertain and still in need of refinement (Drake et al, 2017).…”
Section: Regional Structure Of Fluvial Dissolved Carbonmentioning
confidence: 98%
See 2 more Smart Citations
“…CO 2 supersaturation in streams and rivers is ubiquitous (Raymond et al, ) and in spite of general downstream decline and degassing, CO 2 may never reach equilibrium with the atmosphere because of constant inputs and internal production (Hotchkiss et al, ). Recently, climatic variables (such as NPP) have also been linked to the lateral export of carbon in fluvial networks (Magin, Somlai‐Haase, Schäfer, & Lorke, ; Stackpoole et al, ) as well as directly to fluvial dissolved carbon concentrations at a large scale (Hutchins et al, ).…”
Section: Discussionmentioning
confidence: 99%